2013
DOI: 10.1017/s0007114513003280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the interaction of seaweed extracts containing laminarin and fucoidan with zinc oxide on the growth performance, digestibility and faecal characteristics of growing piglets

Abstract: Seaweed extracts (SWE) rich in laminarin and fucoidan have shown promise as a supplement for weaned piglets. However, successful application in pig nutrition depends on their bioactivity in the presence of additives such as ZnO. In the present study, a 2 £ 2 factorial experiment was carried out to investigate the effect of the interaction between SWE and ZnO on the growth performance, digestibility and faecal characteristics of 192 weaned piglets (6·5 kg). The piglets were penned in groups of 4 (n 12 pens). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 48 publications
(61 reference statements)
4
36
0
Order By: Relevance
“…Previous studies have proved the additive effect of ZnO and in-feed antibiotics for enhancement of growth performance in weaned piglets [5]. However, after the antibiotic ban in European Union, the supplementation of high level of ZnO has increased gradually ever since to control the post-weaning problems that occurred in weaned piglets [15]. Our study showed that ZnO at pharmacological level displayed comparable effects on in-feed antibiotic for improving piglet growth, which suggested that high doses of ZnO remained an effective alternative to in-feed antibiotics in promoting the growth performance of weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved the additive effect of ZnO and in-feed antibiotics for enhancement of growth performance in weaned piglets [5]. However, after the antibiotic ban in European Union, the supplementation of high level of ZnO has increased gradually ever since to control the post-weaning problems that occurred in weaned piglets [15]. Our study showed that ZnO at pharmacological level displayed comparable effects on in-feed antibiotic for improving piglet growth, which suggested that high doses of ZnO remained an effective alternative to in-feed antibiotics in promoting the growth performance of weaned piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, supplementing feed for ruminant cattle with seaweed holds a potential to reduce methane emissions, a possibility that, if confirmed by in vivo and farm-scale experiments, could greatly contribute to mitigate emissions of this powerful greenhouse gas. Prebiotic compounds and essential minerals in seaweeds may furthermore help to enhance livestock production and health (Rey-Crespo et al, 2014;Makkar et al, 2016), as well as substitute the use of antibiotics in the intensive livestock production (O'Doherty et al, 2010;O'Shea et al, 2014). An additional potential benefit of seaweed farming for agriculture is a reported increase in productivity of crops via soil amelioration by nutrient-rich seaweed biochar (Roberts et al, 2015;Zacharia et al, 2015) or seaweed compost (Cole et al, 2016), thereby avoiding emissions involved in synthetic fertilizer production (Smith, 2002).…”
Section: Global Seaweed Production and The Associated Co 2 Uptakementioning
confidence: 99%
“…Dietary supplementation with Laminaria spp. or extracts containing laminarin and fucoidan to weanling pigs improved intestinal health, alleviated common problems occurring post‐weaning, and reduced post‐weaning diarrhea …”
Section: Health Effects In Animalsmentioning
confidence: 99%
“…For instance, an increase in beneficial bacteria such as Lactobacillus spp. and Bifidobacterium in the gastro‐intestinal tract, and a decrease in the numbers of potentially pathogenic bacteria such as Enterobacteria have been reported when adding laminarin or fucoidan to piglet diets . Also, increased villus height and villus height‐to‐crypt depth ratio in the small intestine, increased production of volatile fatty acids, and reduced pH in the hind gut have been reported Different modes of action of these components on gut health have been reported, however, which might be due to differences in the biochemical structures of the two compounds.…”
Section: Health Effects In Animalsmentioning
confidence: 99%